Mediação Literária na Educação Infantil: Um estudo sobre conhecimentos necessários à prática docente - Garcia, Ludmila Ferreira Tristão (2024)
This thesis is premised on literature as an art and a right for all, therefore, it needs to be present in schools from Early Childhood Education, the first stage of Basic Education. Our epistemological basis is Historical-Cultural Psychology (PHC). The guiding question of this thesis is: what knowledge do Early Childhood Education teachers need to know and understand to develop socially referenced quality work with literature for children? Our objective is to map which master's dissertations and doctoral theses were produced between the years 2017 and 2022, published in the Brazilian Digital Library of Theses and Dissertations (BDTD) that dealt with the theme of literature in Early Childhood Education and analyze which they are, according to these researches the knowledge that teachers at this stage need to know to develop work of socially referenced quality with literary mediation. The choice of Early Childhood Education is justified because it is the institution where children enter the schooling process. Regarding the theme “literature for children”, it is considered an important possibility for the formation and integral development of children. We therefore analyzed the data collected from theses and dissertations prepared between 2017 and 2022 with the descriptors: reading in Early Childhood Education and literature in Early Childhood Education. In general terms, we identified that the knowledge found in BDTD research was: aesthetic, humanizing, imagination and mediation training. Some guidelines for mediation are listed as methodological knowledge, from welcoming children, preparation in the organization and choice of literary books, to looking and listening attentively to the child's speech. Finally, literature is an essential instrument for the humanization of children, as art and everyone's rights need to be present in pedagogical practices since Early Childhood Education.